Program Kuliah Kerja Nyata Dalam Upaya Meningkatkan Mutu Pariwisata Dalam Mengembangkan UMKM Di Teluk Makmur - Sakban , Sakban; Nur , Muhammad Danil Bakri; Fitri, Aisyah Rahmatul; Hardisakha, Mia Destia (Jurnal Masyarakat Mengabdi, 2024)
UMKM have a strategic role and potential, namely being able to absorb strategies that can increase the productivity of tourism quality in development in Teluk Makmur Village, Medang Kampai District, Dumai City. The purpose of this Real Work Lecture Program is to help the community improve the quality of tourism in developing UMKM in Teluk Makmur. The method used is literature and qualitative descriptive. In this Real Work Lecture Program, the development of UMKM and tourism quality is carried out by promotion and advertising on social media platforms so that many people are interested in tourism.